2013
DOI: 10.1159/000356491
|View full text |Cite
|
Sign up to set email alerts
|

Human NELL1 Protein Augments Constructive Tissue Remodeling with Biologic Scaffolds

Abstract: Biologic scaffolds composed of extracellular matrix (ECM) derived from decellularized tissues effectively reprogram key stages of the mammalian response to injury, altering the wound microenvironment from one that promotes scar tissue formation to one that stimulates constructive and functional tissue remodeling. In contrast, engineered scaffolds, composed of purified ECM components such as collagen, lack the complex ultrastructure and composition of intact ECM and may promote wound healing but lack factors th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 74 publications
(96 reference statements)
0
3
0
Order By: Relevance
“…Previous groups have attached NELL-1 to a biologic scaffold and found that the addition of the protein augmented the constructive remodeling of the tissue. 132 The modification of PPCN with NELL-1 may provide an extremely effective method for the growth of new bone in an injectable form. Such combinations of scaffold materials and NELL-1 should be particularly useful for craniofacial defect repair ( Fig.…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…Previous groups have attached NELL-1 to a biologic scaffold and found that the addition of the protein augmented the constructive remodeling of the tissue. 132 The modification of PPCN with NELL-1 may provide an extremely effective method for the growth of new bone in an injectable form. Such combinations of scaffold materials and NELL-1 should be particularly useful for craniofacial defect repair ( Fig.…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…20,21 NELL1 is a naturally occurring secreted signaling molecule that mediates tissue growth and maturation during fetal development and stimulates healing in skin, muscle, bone, heart and cartilage after acute injury and systemic diseases such as osteoporosis and osteoarthritis. [29][30][31][32][33][34][35][36][37][38] It is essential during the development of epithelial linings of esophagus, gastrointestinal tract and respiratory system. [39][40][41] Fifteen years of basic science research on NELL1 biology demonstrate that exogenous NELL1 has strong anti-inflammatory and pro-tissue healing effects in the skin, muscle, cartilage, and bone ( Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…[39][40][41] Fifteen years of basic science research on NELL1 biology demonstrate that exogenous NELL1 has strong anti-inflammatory and pro-tissue healing effects in the skin, muscle, cartilage, and bone ( Table 1). [31][32][33][34][35][36][37][38][41][42][43] A hallmark of NELL1 activity is the modulation of the pro-inflammatory response in systemic inflammatory diseases and acute tissue injuries. 37,[41][42][43] In contrast to stem cell therapies currently undergoing clinical testing in COVID-19 patients, NELL1 (1) promotes tissue repair without the associated effects of uncontrolled growth and immune system rejection, and (2) is a recombinant protein that does not rely on complex and laborious stem cell resources.…”
Section: Introductionmentioning
confidence: 99%